The Effectiveness of Tax Dispute Resolution through Alternative Dispute Resolution (ADR) compared to Settlement through Criminal Justice: A Business Law Perspective - Loso Judijanto (PT. Anagata Sembagi Education, 2025)
Tax disputes are an inherent legal phenomenon in business practice because they are often born from differences in interpretation between taxpayers and fiscal authorities on tax obligations that must be met. Law No. 14 of 2002 provides a normative basis regarding the scope of tax disputes and establishes the Tax Court as a special forum with the authority to examine and decide cases with the nature of final and binding decisions. However, this litigation mechanism often poses problems due to the formalistic nature and length of the settlement process, resulting in high costs and legal uncertainty that are detrimental to the business world. From a business law perspective, delayed judgments and procedural rigidity not only impact a company's cash flow, but can also damage its reputation and lower investor confidence. This condition shows that there is a tension between the legal certainty offered by the law and business certainty which is the practical need of business actors. Criminalization in resolving tax disputes through criminal channels also poses reputational risks that are counterproductive to the investment climate. Alternative Dispute Resolution (ADR) offers a more flexible, efficient, and collaborative solution that is able to bridge fiscal interests with business sustainability. ADR integration is in line with the principles of fast, simple, and low-cost as mandated by Article 2 of Law No. 14 of 2002, so that it can be a strategic instrument in strengthening legal certainty, increasing voluntary compliance, and maintaining national economic stability.